2014
DOI: 10.1186/1756-3305-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of the sibling species of Anopheles gambiae sensu lato (Diptera: Culicidae) and malaria prevalence in Bayelsa State, Nigeria

Abstract: BackgroundMuch of the confusing ecophenotypic plasticity of Anopheles gambiae sensu lato is attributable to the differential biological traits of the sibling species, with their heterogeneous geographical distribution, behavioral dissimilarities and divergent population dynamics. These differences are critical to their roles in malaria transmission. Studies were, therefore, undertaken on the spatial distribution of these species and malaria prevalence rates in Bayelsa State, September, 2008-August 2010.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…In this study, analysis showed that age group between 35 -44 years had the highest prevalence rate (84.4 %) within the groups, followed by age group 45-54 years with prevalence of 82.5 % (Table 2). This is in concordance with [29] in a similar study, carried out in Bayelsa State, but in contrast to the works of [30] in Ilorin showing the highest prevalence rate in age group 15-20 years. In this study, the prevalence rate amongst the age groups of 55-64 years had a noticeable difference rate of 28 (63.6 %) as shown in Table 2.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, analysis showed that age group between 35 -44 years had the highest prevalence rate (84.4 %) within the groups, followed by age group 45-54 years with prevalence of 82.5 % (Table 2). This is in concordance with [29] in a similar study, carried out in Bayelsa State, but in contrast to the works of [30] in Ilorin showing the highest prevalence rate in age group 15-20 years. In this study, the prevalence rate amongst the age groups of 55-64 years had a noticeable difference rate of 28 (63.6 %) as shown in Table 2.…”
Section: Discussionsupporting
confidence: 92%
“…Further, climaterelated atmospheric conditions, predominantly rainfall as well as temperature, have been considered as the dependent of habitations, hence vector distribution and abundance between high and low elevation regions. Distribution of vectors and parasites has well been facilitated by the movement and migration of people from high land to low land [49]. Furthermore, density and distribution of vector in all regions have largely been influenced by topography.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge in studying malaria risk in Nigeria is the heterogeneity of the prevalence, which is attributed to high variability in climate conditions as well as the landscape [2,16]. Few published studies in Nigeria have linked malaria prevalence to several influencing factors, including climate and environmental conditions [2,10,11,13,15,[17][18][19][20], socioeconomic factors [15,[21][22][23], geographical factors [10,[13][14][15]18,24], and control strategies as well as prevalence of other febrile illnesses [22,[25][26][27]. Additionally, several authors in other malaria endemic countries have investigated the correlation between malaria and important meteorological variables as observed in Venezuela [6][7][8][9], in Zimbabwe [28], in Zambia [29,30], in Côte D'Ivoire [31], in Ghana [32], in Burundi [33], in Ethiopia [34,35] and many more.…”
Section: Introductionmentioning
confidence: 99%